(untitled) (The Review of Diabetic Studies, 2023)
Background: Self-management for type1 diabetes mellitus patients is a real challenge especially in a time of a spreading pandemic. “Ana wa Soukari” is a smartphone application for therapeutic education and insulin doses management. Objectives: Our study evaluated the effectiveness of “Ana wa Soukari” on clinical and biological outcomes of type1 diabetes self-management. Methods: This is a randomized controlled trial including 62 patients. Groupe “A” (Application users) and Group “B” (without application). Primary endpoint was HbA1c after three months’ follow-up. Secondary endpoints were number of hypoglycaemic events and treatment satisfaction which was assessed using the Arabic version of DTSQs questionnaire. Results: Sixty-two patients were included. Their mean age was 15±6,41 years. Sex ratio M/F=1,1. Mean diabetes duration was 4,9±4,3 years. All patients declared using the application at least twice a day. Mean HbA1c levels in Group A and Group B dropped from 8,3%±2,3 and 8,2%±2 respectively at baseline to 7,4%±1,5 and 8%±1,8 at three months’ follow-up. Change in hypoglycaemic episodes was –1,8±2,0(P< 0,001) for Group A and –1,2±1,5(P< 0,001) for Group B. DTSQs scores were significantly higher in group(A) than group(B). Conclusions: Self-management smartphone apps appear to be effective on glycaemic control and should be considered an adjuvant intervention to standard diabetes care.